Interpreting different measures of glomerular filtration rate in obesity and weight loss: pitfalls for the clinician - Jesudason, D R; Clifton, P (International Journal of Obesity, 2012)
To combat the increasing incidence of obesity, much research has been devoted to devising successful strategies for weight loss, including manipulation of diet and gastric surgery. Obesity itself can be associated with renal dysfunction, and the degree of reversibility of this with weight loss has being studied. However, there are significant limitations and flaws in the methods we have available to measure glomerular filtration rate (GFR) in overweight and obese subjects. Obesity is associated with changes in body composition including lean and fat mass. This has implications for assumptions that underpin creatinine-based measures such as creatinine clearance, estimated GFR and other equations devised for obesity including the Salazar–Corcoran equation. These changes in body composition also affect measures of glomerular filtration such as cystatin C and nuclear medicine isotope scans. This article will review the accuracy of these current measures of renal function in the obese and consider the evidence for adjusting for body surface area or adjusting for lean body mass. Finally, the effect of weight loss itself on serial measurements of renal function in a given individual, independent of a true change in renal function, will be reviewed. Ultimately using the Cockcroft–Gault equation with an adjustment for lean body mass seems to be the best measure for renal function in obesity. No method for measuring renal function in situations of weight loss has been shown to be unequivocally superior.